Population pharmacokinetic meta‐analysis of ramucirumab in cancer patients - O'Brien, Lisa (Br J Clin Pharmacol, 2017)
AIMS: Ramucirumab is a human IgG1 monoclonal antibody that specifically binds vascular endothelial growth factor receptor‐2 (VEGFR‐2) and blocks binding of VEGF‐A, VEGF‐C and VEGF‐D. The objective of the analysis was to characterize the clinical pharmacology profile of ramucirumab using a population pharmacokinetic approach. METHODS: A total of 1639 patients with 6427 serum concentrations from 11 Phase 1b, 2 and 3 clinical trials in patients with various cancer indications were included in the analysis. Ramucirumab was administered as an intravenous infusion over 1 h at 8 mg kg(−1) every 2 weeks or 10 mg kg(−1) every 3 weeks. A series of pharmacostatistical models were developed to describe the concentration data. The best model was used to evaluate patient factors for their effect on ramucirumab pharmacokinetics. RESULTS: The pharmacokinetics of ramucirumab were well characterized by a two‐compartment model. Mean population estimates of clearance, volume of distribution and half‐life for a typical 68‐kg patient were 0.0148 l h(−1), 5.30 l and 13.4 days, respectively. A modest relationship was observed between body weight and ramucirumab disposition; clearance and central compartment volume increased with body weight. No other patient characteristics were shown to influence the disposition of ramucirumab in this patient population. CONCLUSIONS: The final model adequately described the concentration–time profile of ramucirumab in patients with a range of cancer indications. The model confirmed that a weight‐normalized dosing regimen is appropriate for ramucirumab therapy. Dose adjustment was not required for patients with mild to moderate renal impairment or mild hepatic impairment.